Effect of Different Cytokinins and Media Types on In vitro Shoot Proliferation of Asparagus racemosus Willd. (Plant Tissue Culture and Biotechnology, 2016)
The evaluation of the effects of different cytokinin concentrations and media types on in vitro shoot proliferation of Asparagus racemosus Willd. is reported. Maximum shoot number and shoot lengths were found with 0.25 mg/l BA which was statistically similar with 0.1 mg/l Kn. Maximum multiplication and growth were found in MS. The protocol could thus be helpful for in vitro mass propagation of A. racemosus.Plant Tissue Cult. & Biotech. 26(2): 151-157, 2016 (December)